Appendix 1.4: Intelligence Assessment, “Philippine Economic Decision Making: The System and the Players” by the Central Intelligence Agency, United States of America, March 1983 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
A profile of Cesar E.A. Virata as a member of the “Gang of Four” economic technocrats—the other three being Central Bank Governor Jaime C. Laya, Minister of Industry and Trade Roberto V. Ongpin, and National Economic Development Authority Director General Placido L. Mapa Jr.—is included in this United States Central Intelligence Agency (CIA) assessment. The CIA generally had a negative view of Virata’s influence, even though he was already at the height of his career in public service as prime minister/minister of finance. Laya’s office was accorded more influence. Excerpts: “Even though he heads the technocracy, Virata’s record suggests that he is among the least dynamic of its members;” “We believe the budget process has become unwieldy under Virata and Budget Minister Manuel Alba, who have yet to adapt the process to the recent growth of public-sector investment spending;” “On balance, we believe the strength of Virata’s political position—and perhaps eventually his ability to make economic policy independently of political pressure—has eroded since early 1982.”